MINDFUL MOTHERHOOD: HYPNOBREASTFEEDING AS A NATURAL SOLUTION TO INCREASE BREAST MILK PRODUCTION - Khalifatunnisak, Alfadefi; Farokah , Atik; Dewi , Ayu Rosita (Indonesian Midwifery and Health Sciences Journal, 2025)
Abstract Background: For newborns, especially in their early years of life, breast milk is the primary and optimal source of nutrition. Stress, anxiety, and fatigue are often experienced by mothers postpartum, which can affect the let-down reflex and breast milk production. Many breastfeeding mothers worry about their milk supply, it can make mental pressure and exacerbate the condition. Therefore, interventions aimed at reducing stress and increasing confidence in breastfeeding can help enhance milk production. Hypnobreastfeeding is one method that has started to gain recognition in recent years as an alternative approach to support the breastfeeding process. Hypnobreastfeeding  can establish mental environments that facilitate the release of oxytocin, which is essential for both the let-down reflex and the production of milk. The purpose of this study is to investigate the impact of hypnobreastfeeding on nursing moms' ability to produce breast milk. Method: Using a pre-test and post-test approach, this study uses a quasi-experimental design to assess how hypnobreastfeeding affects the production of breast milk. Purposive sampling was used to choose 25 nursing moms who had kids between the ages of 0 and 6 months for the research sample. Result: This study uses a quasi-experimental design to assess how hypnobreastfeeding affects the production of breast milk. Purposive sampling was implemented to choose 25 breastfeeding moms who had babies between the ages of 0 and 3 months for the research sample. This research showed a varying increase in breast milk production, with an average increase of around 30-35 ml every pumping. Conclusion: This study suggests that hypnobreastfeeding can help breastfeeding moms produce more breast milk.